Drivers and impacts of land-use change in the Maasai Steppe of Northern Tanzania: An ecological-social-political analysis - Msoffe, F.U.; Kifugo, S.C.; Said, Mohammed Yahya; Neselle, M.O.; Gardingen, P. van; Reid, Robin S.; Ogutu, Joseph O.; Herrero, Mario; Leeuw, Jan de (Informa UK Limited, 2011)
In this article, we discuss the drivers, causes, and impacts of land-use change in the Maasai Steppe of northern Tanzania. Remote sensing data were used to analyze land-use change, and Geographical Information Systems (GIS) was used to link-up with wildlife population dynamics and livestock distribution data derived from aerial censuses. Agriculture increased five fold between 1984 and 2000, while human population increased exponentially from 3.3% p.a. in 1988 to 3.4% p.a. in the same period. Wildlife migratory routes declined from nine in 1964 to five in 2000, out of which three were seriously threatened with blockage by the extensive cultivation. Recurrent droughts and diseases have contributed to the declining livestock economy over the years due to livestock loss and the unpredictable and erratic rainfall has limited their recovery. To reverse the on-going trends in land use, proper land-use plans should be instituted in parallel with community-based wildlife ventures to maintain long-term ecosystem viability.